KUALITAS OOSIT KAMBING KACANG DARI STATUS REPRODUKSI YANG BERBEDA - Hermilinda Parera (Politeknik Pertanian Negeri Kupang, 2019)
This research was aimed to determine the quality of oocytes produced by Kacang goat based on reproductions cycle per ovary. Ovaries were obtained from the slaughterhouses in Kupang. The oocytes were collected by aspiration method, then selected based on quality. The result showed that 300oocytes from 47 ovaries, then grouped into quality of A, B, C, and D, have the average weight with reproduction status of1,56g (+CL+FD), 1,50g (+CL-FD), 1,45g (-CL+FD), 1,45g(-CL-FD), respectively. The percentage of oocyte with quality A, B, C, and D between reproduction status (+CL+FD)(+CL-FD)(-CL+FD)(-CL-FD) (7,3%, 21,05%, 13,6%, 32,63%); (8,2%, 10,3% 20,6%, 53,6%); (7,69%, 7,69%, 41,02%, 43,58%); (7,2%, 10,14%, 33,3%, 49,2%, recpectively). There is no significant difference (P>0,05) between the quality of oocytes from different ovarian status.It can concluded that the average weight of Kacang goat ovaries were 1,45-1,56g.The ovarian reproductive status does not affect the quality of the oocytes. Key words: Reproduction cycle, oocytes quality, ovaryKacang goats, Kupang city.